Additively manufactured metal foot orthotics and educating tomorrow's engineering entrepreneur: lessons learned from NSF I-Corps. (16th February 2021) - Liu, Yucheng; Stranburg, Tyler; Chander, Harish; Bell, James; Knight, Adam
The National Science Foundation (NSF) Innovation Corps (I-Corps) teams program was designed to provide learning environments and entrepreneurship training for graduate students and researchers to translate and commercialise their fundamental research results through customer discovery and starting new companies. A Mississippi State University (MSU) team participated in this program with their preliminary design of metal-based arch wedge supports (AWSs) produced using additive manufacturing (AM) methods and the results obtained from the team's NSF I-Corps site program. During the seven-week I-Corps program, 102 interviews were conducted and the team gained a deep understanding of customers, partners, and markets. Based on the intensive interviews with potential customers and partners, the team has formed a business canvas model and decided to pursue the commercialisation of applying AM methods to produce custom and semi-customised foot orthotics with high durability at low cost. A PhD student, who is also the entrepreneur lead of this team, has gained substantial entrepreneurship skills through the I-Corps training program.